2016
DOI: 10.1186/s12864-016-2600-y
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression comparison of resistant and susceptible Atlantic salmon fry challenged with Infectious Pancreatic Necrosis virus reveals a marked contrast in immune response

Abstract: BackgroundInfectious Pancreatic Necrosis (IPN) is a highly contagious birnavirus disease of farmed salmonid fish, which often causes high levels of morbidity and mortality. A large host genetic component to resistance has been previously described for Atlantic salmon (Salmo salar L.), which mediates high mortality rates in some families and zero mortality in others. However, the molecular and immunological basis for this resistance is not yet fully known. This manuscript describes a global comparison of the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
59
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 83 publications
(114 reference statements)
8
59
2
Order By: Relevance
“…This is in contrast to what was seen in IHNV, and previous studies that show a positive relation between mortality caused by IPNV and virus load in Atlantic salmon, i.e. higher mortalities were associated with higher viral loads in susceptible fish or in fish infected with more virulent isolates (Skjesol et al, 2011; Reyes-Lopez et al, 2015; Robledo et al, 2016). It is important to point out that both isolates from genogroup 5 had contained high virulence marker, Thr 217 and Ala221, in their VP2 sequence; whereas isolates from genogroup 1 had the avirulent motif, Pro 217 and Thr 221 .…”
Section: Discussioncontrasting
confidence: 99%
“…This is in contrast to what was seen in IHNV, and previous studies that show a positive relation between mortality caused by IPNV and virus load in Atlantic salmon, i.e. higher mortalities were associated with higher viral loads in susceptible fish or in fish infected with more virulent isolates (Skjesol et al, 2011; Reyes-Lopez et al, 2015; Robledo et al, 2016). It is important to point out that both isolates from genogroup 5 had contained high virulence marker, Thr 217 and Ala221, in their VP2 sequence; whereas isolates from genogroup 1 had the avirulent motif, Pro 217 and Thr 221 .…”
Section: Discussioncontrasting
confidence: 99%
“…This would suggest that WB strain type isolates require the same or even less viral load than Sp strain to cause greater mortality in rainbow trout. This is in contrast to what was seen in IHNV, and in previous studies with IPNV that show a positive relation between mortality and virus load in Atlantic salmon; that is, higher mortalities were associated with higher viral loads in susceptible fish or in fish infected with more virulent isolates (Reyes-Lopez et al, 2015;Robledo et al, 2016;Skjesol et al, 2011). It is important to point out that both isolates from genogroup 5 had contained high virulence marker, Thr 217 and Ala 221, in their VP2 sequence, whereas isolates from genogroup 1 had the avirulent motif, Pro 217 and Thr 221 .…”
Section: Discussioncontrasting
confidence: 98%
“…However, we were unable to obtain higher viral titres without increasing the number of passages of the isolates in cell culture. Nevertheless, several researchers have used the same dose used in this study in immersion challenges and have obtained considerably higher mortalities in rainbow trout and Atlantic salmon (Okamoto, Seno, Taniguchi, & Sano, 1987;Robledo et al, 2016;Skjesol et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, a completely different immune reaction was observed in other resistant and susceptible families of Atlantic salmon. The vast majority of innate immune response genes, including IFNα , IFNγ , Mx , ISG15 , viperin and Gig2 , had higher expression in whole fry of susceptible family than in resistant family [92]. These different dynamical changes of IFN system genes among different Atlantic salmon families might be due to different tissues used (head-kidney in the two formers and whole fry in the latter) or different families [92], which indicated that fish immune response against virus is complex and possesses a species-specific or tissue-specific manner.…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of innate immune response genes, including IFNα , IFNγ , Mx , ISG15 , viperin and Gig2 , had higher expression in whole fry of susceptible family than in resistant family [92]. These different dynamical changes of IFN system genes among different Atlantic salmon families might be due to different tissues used (head-kidney in the two formers and whole fry in the latter) or different families [92], which indicated that fish immune response against virus is complex and possesses a species-specific or tissue-specific manner. Further studies are necessary to verify the changes of these important DEUs identified in this study at different stages after infection and to reveal their regulative mechanisms behind differential expression between gibel carp resistant and susceptible clones.…”
Section: Discussionmentioning
confidence: 99%